2016
DOI: 10.3346/jkms.2016.31.12.1937
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies against Hepatitis A and Hepatitis B Virus in Intravenous Immunoglobulin Products

Abstract: The worldwide seroprevalence of hepatitis A virus (HAV) and hepatitis B virus (HBV) has changed over the last two decades, indicating a declining incidence of HAV and HBV infections. Therefore, vaccinations against HAV and HBV are recommended for unimmunized people before traveling to an endemic area. Unfortunately, primary antibody deficiency (PAD) patients can only obtain humoral immunity through intravenous immunoglobulin G (IVIG) replacement and not from vaccination because of a defect in antibody producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 35 publications
(42 reference statements)
1
19
0
Order By: Relevance
“…Results for Japanese and Korean products from Lee et al seem below this range, particularly for HBV. 45 The discrepancies between that study and the earlier studies may be due to technical differences in the way the assays were performed, differences in immunization practices in different countries, or other factors, and should be studied further. In studies in which results from multiple lots of the same product were reported, the coefficients of variation amongst the lots are generally within 25%.…”
Section: Antibodies Against Hepatitis a Virus And Hepatitis B Virusmentioning
confidence: 80%
See 4 more Smart Citations
“…Results for Japanese and Korean products from Lee et al seem below this range, particularly for HBV. 45 The discrepancies between that study and the earlier studies may be due to technical differences in the way the assays were performed, differences in immunization practices in different countries, or other factors, and should be studied further. In studies in which results from multiple lots of the same product were reported, the coefficients of variation amongst the lots are generally within 25%.…”
Section: Antibodies Against Hepatitis a Virus And Hepatitis B Virusmentioning
confidence: 80%
“…As shown in panel B, neutralizing anti‐HAV titers in final containers of a single IgG product show a similar and highly significant (p < 0.0001) difference depending on whether the product was made from plasma from EU (left) vs US plasma (right) . Despite the data showing that IgG derived from US plasma has only half as much neutralizing antibody as EU‐derived IgG, even the titer in the US product, 14.6 IU/mL, is > 1000 fold higher than that needed to provide a minimal protective level of 10 mIU/ml in recipients' plasma …”
Section: Antibodies Against Hepatitis a Virus And Hepatitis B Virusmentioning
confidence: 94%
See 3 more Smart Citations